PEMANFAATAN APLIKASI PENGGAMBAR DIAGRAM ALIR (FLOWCHART) SEBAGAI BAHANAJAR UNTUK MATA KULIAH SISTEM AKUNTANSI DI FAKULTAS EKONOMI PADA PERGURUAN TINGGI SWASTA DI KOTA MEDAN - Seprida Hanum (KITABAH: Jurnal Akuntansi dan Keuangan Syariah, 2017)
Learning method use information technology tools in the subject of Accounting System can improve learning and student understanding of the material flow chart. Utilization draftsman flowchart applications for courses in Accounting Systems is forms of media use of information technology based learning. This research aims to apply information technology based instructional media at the time of learning for courses on subjects Accounting System to the flow chart in terms of enhancing the ability and understanding of students. so expected to provide a new concept of learning by applying information technology to subjects Accounting System. This research was used in an attempt to implement innovative concepts in learning to increase the interest of students to study the flow chart in a different way through the use of the application as a medium of learning